2021
DOI: 10.1088/2515-7620/abffa4
|View full text |Cite
|
Sign up to set email alerts
|

Back to the fields? Increased agricultural land greenness after a COVID-19 lockdown

Abstract: In response to the 2020 COVID-19 pandemic, policymakers worldwide adopted unprecedented measures to limit disease spread, with major repercussions on economic activities and the environment. Here we provide empirical evidence of the impact of a lockdown policy on satellite-measured agricultural land greenness in Badung, a highly populated regency of Bali, Indonesia. Using machine learning and satellite data, we estimate what the Enhanced Vegetation Index (EVI) of cropland would have been without a lockdown. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Their findings help evaluate the impact of Covid-19 on China's agricultural sector, which is promotive to formulating effective agricultural policy and ensuring food security. Hammad et al [25] provided empirical evidence of the after-effects of the lockdown policy on agricultural land greenness in Bali, Indonesia, using ML and SRS data and resulting in an Enhanced Vegetation Index (EVI) croplands. However, [26] showed that India had a good cropping season during the lockdown and post-lockdown periods.…”
Section: ) Agriculture Monitoringmentioning
confidence: 99%
“…Their findings help evaluate the impact of Covid-19 on China's agricultural sector, which is promotive to formulating effective agricultural policy and ensuring food security. Hammad et al [25] provided empirical evidence of the after-effects of the lockdown policy on agricultural land greenness in Bali, Indonesia, using ML and SRS data and resulting in an Enhanced Vegetation Index (EVI) croplands. However, [26] showed that India had a good cropping season during the lockdown and post-lockdown periods.…”
Section: ) Agriculture Monitoringmentioning
confidence: 99%
“…Scientists have used Machine Learning and Satellite Imagery to monitor tropical forest carbon stocks (Csillik et al, 2019), to identify and classify the direct drivers of deforestation (Irvin et al, 2020) and to estimate the effect of public policies on agricultural productivity (Hammad et al, 2021). Machine Learning algorithms provide unprecedented and promising results thanks to their ability to find patterns underlying the complex nonlinear relations that characterised environmental variables.…”
Section: Introductionmentioning
confidence: 99%